Síntese e caracterização de nanopartículas semicondutoras de ZnO@Carbono com estrutura tipo núcleo-casca - Martins, Tiago Almeida (Universidade Federal de São Carlos, 2021)
In these study, nanoparticles with a core-shell structure of oxide zinc-carbon (ZnO@Carbon) were synthesized using the simple thermal decomposition method of Zn(CH3CO2)2•2H2O in a conventional electric furnace and a hybrid heat/microwave furnace. The ZnO@Carbon powders were characterized by structural, optical and photocatalytic techniques, aiming to analyze the structural order-disorder effects of their components. Initially, only samples synthesized by the conventional electric furnace were studied and it was observed that the order or disorder level of both the ZnO and the carbon shell dramatically affect the photoluminescent and photocatalytic properties of the ZnO@C composites. Furthermore, was clarify that the photocatalytic mechanisms of some particles of ZnO@Carbon is dependent of the type of light used (UV or visible). ZnO@Carbon particles were synthesized through a hybrid heat/microwave furnace and an electric furnace at the same temperatures. The microwaves generated changes in morphology, crystallinity and carbon proportion of particles. The hybrid furnace also reduce the minimal synthesis temperature for synthesis of ZnO@Carbon particles, thus obtaining a sample with 4 times the concentration of carbon obtained in a conventional electric oven. These sample allow understand better how changes in carbon materials affect the photoluminescent profiles and the photocatalytic activity of ZnO@Carbon particles, in addition to enabling a better adsorption capacity of ZnO@Carbon particles, generated by the greater composition of mass of carbon in the particles.
Synthesis and characterization of ZNO@Carbon semiconductor nanoparticles with core-shell structure
Keywords: Óxido de Zinco; Carbono; Núcleo Casca; ZnO; Carbon; Core-Shell; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA